In-plane benzene incorporated g-C3N4 microtubes: Enhanced visible light harvesting and carrier transportation for photocatalytic CO2 reduction. (15th October 2022) - Wang, Wen-Feng; Zhang, Yong-Kang; Feng, Lie-Feng; Li, Hong-Ru; He, Liang-Nian
Graphical abstract: Highlights: Benzene ring incorporated g-C3 N4 microtubes are fabricated. This material has improved light harvesting and carrier separation efficiency. It can be applied in photocatalytic CO2 reduction with Co(bpy)3 Cl2 as co-catalyst. The catalytic system presents high efficiency and selectivity to CO. Stability is the most attractive feature for this material. Abstract: As a promising material for photocatalytic CO2 reduction, graphitic carbon nitride (CN) and its modification has attracted significant attention. In this work, the in-plane benzene incorporated g-C3 N4 microtubes were fabricated via a hydrothermal self-assembly and subsequent thermal polymerization. It is revealed that introducing the π electron-rich benzene ring into the planar structure of g-C3 N4 can improve the availability of π electron and create the local asymmetry of heptazine structure. As a result, the separation and transportation of photogenerated charges are improved. Furthermore, the modified g-C3 N4 possesses relatively narrow band gap and enhances light absorption. When the in-plane benzene modified g-C3 N4 microtubes were applied to photocatalytic CO2 reduction with Co(bpy)3 Cl2 as co-catalyst, a CO yield up to 322.66 μmol·g −1 ·h −1 was obtained, which was two times in comparison with the pristine g-C3 N4 . This work confirms the effectiveness of in-plane benzene modification and 1D hollow structure formation in improving the photoelectric performance of g-C3 N4 . Besides, it provides an efficient photocatalytic CO2 reduction protocol with nonmetallic semiconductor material and earth-abundant metal co-catalyst.